Detection of Salmonella spp. in ready-to-eat foods: use of the biomolecolar method BAXR in association with traditional microbiology (Italian Journal of Public Health, 2005)
In order to evaluate the presence of Salmonella spp. in ready-to-eat foods, sixty-nine samples were analyzedusing the BAXRsystem for Screening/Salmonella, a quick method based on PCR technology, andconventional culture procedures. Both methods showed the absence of Salmonella spp. in all samples andpositive results for one sample artificially contaminated by a strain of Salmonella enteritidis, showing a fullagreement. The biomolecolar system adopted appeared to be useful to supplement existing tests for thefinal identification of rough presumptive Salmonella isolates, for the rapid screening of food samples andthe quick identification of Salmonella spp.
Keywords: Salmonella; ready-to-eat foods; PCR